Kleine − Levin syndrome: An ayurvedic perspective - Prasad Mamidi; Kshama Gupta (Wolters Kluwer Medknow Publications, 2022)
Kleine − Levin syndrome (KLS), also known as sleeping beauty syndrome, is characterized by the classic triad of hypersomnia, hyperphagia, and hypersexuality. It is an intriguing and severe disease with no clear etiology or management. The present study aims for better understanding of KLS according to Ayurveda and to propose an Ayurvedic management protocol for it. The present study has explored the similarity between KLS and an Ayurvedic diagnostic entity, Bhutonmada, or Grahonmada. Bhutonmada is the most suitable provisional diagnosis for the patients of primary KLS. Yaksha Grahonmada is the most perfect match for KLS though some of the clinical features are dissimilar. Bhutonmada Chikitsa as explained in Ayurvedic texts could be implemented to manage KLS. Panchakarma (Ayurvedic detoxification) procedures, Daiva Vyapashraya Chikitsa, Sattvavajaya Chikitsa, Achara Rasayana along with medications may play an important role in the management of KLS. Hypersomina episodes of KLS could be managed with Ati Nidra Chikitsa. The present work provides new insights and also paves the path for future research works for better understanding and managing the KLS in Ayurveda.